The effect of the Ambulatory Integration of the Medical and Social (AIMS) model on health risk and depression. (28th May 2022) - Rizzo, Victoria M.; Rowe, Jeannine M.; Han, Woojae; Kang, Suk-Young; Ewald, Bonnie; Rothschild, Steven K.; Golden, Robyn
ABSTRACT: Social needs are factors for health risk and depression that may negatively impact health outcomes and costly services use. Care management addresses social needs that can reduce health risk and depression. An exploratory study of the 5-step Ambulatory Integration of the Medical and Social Model (AIMS) was conducted to examine the effect of steps completed as part of AIMS on patients' depression and health risk outcomes at 6-months. Results reveal steps central to AIMS are significantly related to lower depression and health risk, suggesting AIMS is a valuable intervention for reducing health risk and depression.